Influence of superabsorbent polymers (SAPs) type and particle size on the performance of surrounding cement-based materials. (8th February 2021) - Tan, Yawen; Lu, Xiaosong; He, Rui; Chen, Huaxin; Wang, Zhenjun
Highlights: The moisture diffusion areas of SAPs in the cement-based material were analyzed at different ages. The effect of the moisture released from SAPs on the mechanical properties, micro-hardness, and hydration was characterized. The incorporation of non-ionic SAP with 200 mesh can achieve a good internal curing effect. The addition of SAP promotes the further hydration and increases the micro-hardness of surrounding cement-based material. The addition of SAP has an influence on the crystal form of portlandite and decreases the average crystal sizes of alite. Abstract: Superabsorbent polymer (SAP) has been considered as the most promising internal curing material due to its excellent internal curing efficiency. SAP type and particle size are important factors influencing the performance of cement-based materials. In this paper, cement paste was prepared by incorporating swollen SAP-SA and SAP-AA (sodium acrylate type of polymer and acrylic acid of polymer) with different particle sizes, 100 mesh, 120 mesh, 140 mesh, 170mesh, and 200 mesh, respectively. Firstly, the moisture diffusion areas of SAPs were compared and analyzed at different ages, and then the effect of the moisture released from SAPs on the mechanical properties, micro-hardness, and hydration was characterized and investigated. The results indicate that the 28-day moisture diffusion area of per gram of dry SAP-SA swollen with red ink in testing cement paste is about 40.3 cm 2 to 50.8 cm 2, while for each gram of dry SAP-AA, the 28d moisture diffusion area in testing cement paste is about 52.0 cm 2 to 59.6 cm 2 . The cement pastes with SAP-SA and SAP-AA presents the higher 28d compressive strength at particle sizes of 140 mesh and 200 mesh, respectively. For the SAP-SA and SAP-AA of the same particle size of SAP-SA and SAP-AA, the incorporation of SAP-AA is more beneficial to the development of 28-day compressive strength and internal curing water diffusion of specimen than that of SAP-SA. The microhardness values of the specimens are closely related to the cumulative step length. The average crystal size of alite in the specimen containing SAP-AA200 is smaller than that in the specimen containing SAP-SA200 .